Musiikkilähtöiset menetelmät työhyvinvoinnin tukena -systemaattinen kirjallisuuskatsaus - Salonen, Eveliina (2024)
This systematic literature review brings together information about music-based methods that have been used in the research of occupational well-being in the 21st century. The thesis also maps the methodological-theoretical frameworks from the literature.